Inflammatory Markers and Procalcitonin Predict the Outcome of Metastatic Non-Small-Cell-Lung-Cancer Patients Receiving PD-1/PD-L1 Immune-Checkpoint Blockade - Nardone, Valerio; Giannicola, Rocco; Bianco, Giovanna; Giannarelli, Diana; Tini, Paolo; Pastina, Pierpaolo; Falzea, Antonia Consuelo; Macheda, Sebastiano; Caraglia, Michele; Luce, Amalia; Zappavigna, Silvia; Mutti, Luciano; et al. (Frontiers in Oncology, 2021)
Peripheral-immune-checkpoint blockade (P-ICB) with mAbs to PD-1 (nivolumab and pembrolizumab) or PD-L1 (atezolizumab, durvalumab, avelumab) alone or combination with chemotherapy represents a novel active treatment for mNSCLC patients. However, this therapy can be associated to immune-related adverse events (irAEs) and high cost. Therefore, finding reliable biomarkers of response and irAEs is strongly encouraged to accurately select patients who may potentially benefit from the immuno-oncological treatment. This is a retrospective multi-institutional analysis performed on ninety-five mNSCLC patients who received real-world salvage therapy with nivolumab or atezolizumab between December 2015 and April 2020. The outcome of these patients in term of PFS and OS were evaluated in comparison with different serum levels of C-reactive protein (CRP), Erythrocyte Sedimention Rate (ESR) and Procalcitonin (PCT) by performing Kaplan Meier and Log-rank test and multivariate analysis. We found that high baseline levels of CRP, ESR, and PCT were strongly predictive of poor outcome (P<0.05) with the worse prognosis detected in those patients with a baseline levels of both ESR and PCT over the pre-established cut off (median OS recorded in patients with no marker over the cut off vs. those with just one marker over the cut off vs. those with both markers over the cut off: 40±59 vs. 15.5±5.5 vs. 5.5±1.6 months, respectively; P <0.0001) Our results suggest the predictive value of systemic inflammation and suggest a potential role of PCT in predicting a poor outcome in mNSCLC receiving PD-1/PD-L1 blocking mAbs. This finding also suggests a potential role of subclinical bacterial infections in defining the response to PD-1/PD-L1 blocking mAbs that deserves further and more specific investigations.